Pengaruh Media Visual Terhadap Keaktifan Belajar Siswa Pendidikan Agama Kristen Kelas V SD Negeri 10 Hutagalung Tahun Pembelajaran 2022/2023 - Sutri Natalia Nababan; Boho Pardede; Dame Taruli Simamora; Johari Manik; Taripar Aripin Samosir (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
This research aims to find out the influence of visual media on the learning activity of Christian religious education students in class V at SD Negeri 10 Hutagalung for the 2022/2023 academic year. This research uses quantitative descriptive statistical methods, with a population of 30 people and a sample of 30 people. Data was collected using a closed questionnaire instrument of 30 items, namely 17 items for variable X and 13 for variable Y which was tested on 30 students who were not research respondents. The results of data analysis show that there is a positive and significant influence of visual media on the learning activity of class V Christian religious education students at SD Negeri 10 Hutagalung, Harian District, Samosir Regency for the 2022/2023 Academic Year: a) the positive relationship test is obtained from (r_xy) = 0.748 > r_ (table (α=0.05,n=30))= 0.361. b. Testing a significant relationship obtained a t_(calculated) value of 5.978, it is known that t_(table) in α=0.05 n-2=30-2=28 is 1.701. 2) Influence test: Regression equation test Y ̂= 13.40+ 0.50x. b) Regression determination test (r^2)= 55.9%. 3) Test the hypothesis using the F test, obtained f_count > f_(table ) namely 35.04 > 4.24. Thus Ha is accepted and H0 is rejected.